Metabolic reprogramming in pulmonary arterial hypertension: is it a cancer-like disease?. (14th October 2021) - Ferreira, C; Abreu, M; Castro, G; Goncalves, L; Baptista, R; Girao, H
Abstract: Background: Idiopathic pulmonary arterial hypertension (iPAH) is a rare and chronic disease associated with poor outcomes. Previously considered a disease restricted to the pulmonary circulation, PAH is now being recognized as a systemic disorder that is associated with metabolic dysfunction. The aim of this study is to analyze the metabolic reprogramming in the lung and peripheral blood mononuclear cell (PBMCs) of iPAH patients and explore their potential roles in PAH pathophysiology. Methods: Five independent datasets, containing transcriptomic data of human PBMCs (GSE22356 and GSE33463) and lung (GSE48149 GSE113439 and GSE117261) samples, from 139 iPAH patients and 96 healthy controls, were downloaded at the GEO database. In each dataset, the samples were normalized and a pair-wise comparison between control and iPAH samples was performed using limma package, for the R programming language. Genes with a p-value lower than 0.05 were considered differentially expressed between the two groups. A subset of metabolism related genes was selected, and their expression was compared across the datasets. Results: Among the 13 genes with differential expression identified, only 10 had a coherent expression across all datasets (Figure 1). Firstly, we report an association with insulin resistance through impairment of PI3K signaling in iPAH patients, by expressing lower levels of the heterodimer PIK3CD and regulatory PIK3IP1 and PIKR1 subunits in PBMCs, and by expressing higher levels of its downstream targets in the lung (TBC1D4). However, more extensive metabolic dysfunction was observed. A significant glycolytic shift in the lung and PBMCs was present, as a consequence of deregulation in genes involved in aerobic glycolysis and decreased fatty acid oxidation, namely increased expression of PD1K and lower levels of expression of LDHB. The findings of decreased SLC25A1 protein in both PBMCs and lung suggest impairment of the tricarboxylic acid (TCA) cycle flux in PAH. Additionally, SLC1A5 highlights the involvement of glutamine metabolism and glutaminolysis derangements in PAH. Conversely, SREBP1 is involved in sterol biosynthesis and lower levels in PMBCs results in impaired resolution of inflammatory responses. Finally, although the role of autophagy in iPAH is complex, higher levels of expression of ATG13 in PBMCs and lower levels in the lung confirm autophagy deregulation in iPAH. Interestingly, all the metabolic pathways identified (Figure 2) are hallmarks of the metabolic reprogramming seen in cancer cells, a finding already suggested by the clonal proliferation of pulmonary artery smooth muscle cells described in plexiform lesions. Conclusion: Our results provide novel insights into the metabolic regulation in iPAH. Molecularly, these cells exhibit many features common to cancer cells, suggesting the opportunity to exploit therapeutic strategies used in cancer to treat iPAH. FUNDunding Acknowledgement: Type of funding sources: None.